2019
DOI: 10.3389/fimmu.2019.01414
|View full text |Cite
|
Sign up to set email alerts
|

What Defines NK Cell Functional Fate: Phenotype or Metabolism?

Abstract: NK cells are capable of an array of functions that range widely from their classic anti-tumor and anti-viral cytotoxic effector functions, to their critical regulatory roles in controlling inflammatory immune responses and promoting tissue growth. However, the mechanisms that polarize NK cells to these distinct and opposing functions are incompletely understood. NK cell functional subsets are primarily identified and studied based on phenotype, which has served as an accessible means for profiling NK cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 91 publications
3
95
0
Order By: Relevance
“…Our result that the early release of IFNγ and CCL3/4/5 from short-term IL-15 primed and IL-12/IL-18 stimulated human NK cells is unaffected by simultaneous glucose deficiency and hypoxia supports the concept of metabolic autonomy during regulatory NK cell polarization [65], specifically, during the early innate immune response (Supplemental Discussion). We propose that cytokine induced switching to glycolysis and OxPhos to support cytotoxic activity [43,44] succeeds in a time-dependent manner.…”
Section: Resultssupporting
confidence: 77%
“…Our result that the early release of IFNγ and CCL3/4/5 from short-term IL-15 primed and IL-12/IL-18 stimulated human NK cells is unaffected by simultaneous glucose deficiency and hypoxia supports the concept of metabolic autonomy during regulatory NK cell polarization [65], specifically, during the early innate immune response (Supplemental Discussion). We propose that cytokine induced switching to glycolysis and OxPhos to support cytotoxic activity [43,44] succeeds in a time-dependent manner.…”
Section: Resultssupporting
confidence: 77%
“…Metabolic studies have also revealed a new aspect of NK cell biology and differentiation based on the influence of metabolic factors outside of traditional routes of cellular influence, and these studies have been well-reviewed recently ( 279 282 ). Indeed, large differences in metabolic processes have been identified within NK cell subsets.…”
Section: Next-generation Approaches To Studying Nk Cell Adccmentioning
confidence: 99%
“…Specific stimulation or induction of the anti-tumor capacity of certain NK cell subpopulations, such as memory-like or adaptive NK cells, might achieve more powerful efficacy and better clinical outcomes. Recently, increasing evidence has highlighted the crucial role of the cellular metabolic program in directing the development, survival, proliferation, and function of immune cells, and tumors and metabolic products in the TME induce the dysfunction and exhaustion of T and NK cells by modulating cell metabolism (40,(151)(152)(153)(154). Novel strategies might emerge from increased knowledge of the metabolic requirements of activated NK cells through targeting metabolic reprogramming and related pathways or factors to improve NK cell function more effectively within the TME (155).…”
Section: Perspectivesmentioning
confidence: 99%